Separation of short and medium‐chain fatty acids using capillary electrophoresis with indirect photometric detection: Part I: Identification of fatty acids in rat feces. Issue 19 (2nd August 2021) - Pham, Uyen; Alvarado, Luis; Suess, Gregory J.; Shamsi, Shahab A.; Frantz, Kyle
Abstract: Short and medium‐chain fatty acids (SMCFAs) are known as essential metabolites found in gut microbiota that function as modulators in the development and progression of many inflammatory conditions as well as in the regulation of cell metabolism. Currently, there are few simple and low‐cost analytical methods available for the determination of SMCFA. This report focuses on SMCFA analysis utilizing CE with indirect photometric detection (CE‐IPD). A ribonucleotide electrolyte, 5'‐adenosine mono‐phosphate (5'‐AMP), is investigated as an IPD reagent due to its high molar absorptivity and dynamic reserve compatible with separation and detection of SMCFA. The operating parameters like the composition of organic solvent, millimolar concentrations of the complexing agent (alpha‐cyclodextrin), 5'‐AMP and non‐absorbing electrolyte (boric acid), as well as the applied voltage, are optimized for resolution, efficiency, and signal‐to‐noise ratio. A baseline resolution of all nine SMCFAs is achieved in less than 15 min. Additionally, the developed CE‐IPD method shows promising potential to identifying SMCFA in rat fecal supernatant. The presented analytical assay is simple, economical, and has considerably good repeatability. The intraday and interday RSD of less than 1 and 2% for relative migration time, as well as less than 14 and 15% for peak area, respectively, were obtained for SMCFA in fecal solution.